Analysis of the associations between contextual variables and match running performance in croatian first division soccer - Jerkovic, Z.; Modric, T.; Versic, S. (SportMont, 2022)
It has been hypothesized that contextual variables (i.e. match location, opponents` level) could be important determinants of running performance (RP) in soccer matches, but empirical studies provided inconsistent evidences. This study aimed to investigate the associations between contextual variables (CV) and RP in Croatian soccer players. Players` RP (n=193) were evaluated, and used as cases in this study. CV included match outcome (win-draw-loss), opponent`s level (higher vs. lower ranked), and match location (home-away). RP were measured by global position- ing system during the soccer matches in seasons 2018/19 (n=14) and 2019/20 (n=15) of Croatian first division, and included: the total distance covered, low-intensity (19.8 km/h), high-speed running (19.8-25.1 km/h) and sprinting (>25.2 km/h). Results indicated significantly greater amount of distance covered in running zone for away matches (F-test: 7.83, p0.05). Lowest total-, low- and running-zone distances were evidenced in won matches (9893±896 m, 8035±614 m and 1241±312 m, respectively), followed by drawn matches (10298±913 m, 8287±838 m and 1363±320 m, respectively) and lost matches (10355±1052 m, 8279±742 m and 1406±343 m, respectively). This study demonstrated that (i) won matches were characterized by lower RP, (ii) association between RP and match location was limited, (iii) RP was not related to the opponents` level.